SQL server 7 developer's guide - Otey, Michael (Osborne McGraw-Hill, 1999)
SQL server 7 developer's guide combines start-to-finish coverage of core SQL server 7 concepts with step-by-step programming examples in text and on CD-ROM. It also provides special tutorials on relational database concepts and building SQL statements - plus a complete guide to using Visual Basic for SQL server application development